CALCULATION OF THE COMPOSITION OF FRACTIONATED SOLID AS DEDUCED FROM CHEMICAL PROFILES IN THOLEIITIC LAVA - MacLean W.H. (My University, 2000)
The composition of solid precipitated from cooling magma is calculated from chemical differentiation profiles and an incompatible element monitor of fractionation. In a period of cooling, magma evolves to a derivative liquid and a solid; liquid compositions are obtained from the chemical profiles, and the fractionation interval via the incompatible element and the Rayleigh distillation equation. The composition of the solid, the only unknown, can be calculated for both equilibrium and continuous fractionation models. A sequence of low-K tholeiitic laves (basalt to rhyolite) from an Archean greenstone belt in northwestern Quebec are used to describe the procedure. Chemical trends in the lava exhibit strong iron enrichment followed by depletion and evolution to rhyolite. Trends in the calculated solid are amplified relative to lava, and bulk distribution coefficients, normative minerals, mg-number, and other parameters also show significant divergence. Oxidation state and amount of "trapped liquid" have important effects on solid composition. Solids have notably more basic chemical compositions than coexisting liquids, and this produces a "lag" in differentiation indices between the two. The high values of bulk distribution coefficients calculated for Fe, Ti and P (D ~ 3 to 4+) in late stages of fractionation make it possible to produce the extremely Fe-Ti-P-rich solid fractions in layered igneous complexes from quartz-normative liquids.
Keywords: Archean; Precambrian::Archean; Докембрий::Архей